IAEA inter-laboratory comparisons of geothermal water chemistry: critiques on analytical uncertainty, accuracy, and geothermal reservoir modelling of Los Azufres, Mexico - Verma, M. P. (Journal of Iberian Geology, 2013)
The results of International Atomic Energy Agency (IAEA) inter-laboratory comparison program reported in the literature during 1992 and 2004 were analyzed to estimate analytical uncertainty in the geochemical analysis of geothermal waters. Statistical data treatments for the detection and elimination of outliers and extremums were performed using five methods: (i) data visualization (or raw data statistics); (ii) mean ( x ) and standard deviation (s) calculation after eliminating outliers with x ± 2s ; (iii) median and median absolute difference (MAD); (iv) Huber method; and (v) single-outlier type multiple test method involving Dixon, Grubbs, skewness and kurtosis tests at 99% confidence level. The results are reported in scientific notation with one significant digit of uncertainty. A comparative study of all the five statistical data treatment methods suggests that the fifth method provides better results for the statistical analysis of experimental measurements. A preliminary evaluation for the analytical accuracy of geochemical analysis of geothermal waters, prepared by dissolving 4.585 g CaCl2 (98.2%), 16.5 g NaCl (99.9%), 3.58 g MgCl2 (99.0%), 0.74 g Na2SO4 (99.0%) and 0.95 g KCl (99.5%) in 1 liter of solution, is presented. The analysis of Na+ and K+ are reasonably accurate, while Mg2+ and SO4 2- have high inaccuracy. The accuracy of Ca2+ and Cl- analyses is in-between. A systematic analysis of the results suggests that the present inaccuracy in the measurements of Mg2+, Ca2+, SO4 2- and Cl- are probably associated with the sample preparation. The relations between the coefficient of variation (i.e. % analytical uncertainty) and concentration of each element are derived, which are used for the propagation of uncertainty in the geochemical calculations of geothermal systems. The uncertainty propagation procedure is illustrated in the calculation of Los Azufres geothermal reservoir temperature and vapor fraction. The uncertainty in the estimated temperature is ±20 K, which means that the changes in the geothermal reservoir fluid characteristics during its exploitation are generally within the uncertainty.